Monitoring of hepatitis E virus RNA during treatment for chronic hepatitis E virus infection after renal transplantation. Issue 2 (8th February 2021) - Affeldt, Patrick; Di Cristanziano, Veronica; Grundmann, Franziska; Wirtz, Maike; Kaiser, Rolf; Benzing, Thomas; Stippel, Dirk; Kann, Martin; Kurschat, Christine
Abstract: Background: Recently, chronic hepatitis E virus (HEV) infections gained increasing attention as a possible cause for elevated liver enzymes of unknown origin and liver cirrhosis in solid organ transplant recipients. Reduction of immunosuppressive therapy and/or use of antiviral drug ribavirin have been established as possible treatment strategies. Methods: The efficacy of dose reduction of mycophenolic acid (MPA) and ribavirin therapy was retrospectively analyzed in eight renal transplant patients of our outpatient clinic who were diagnosed with HEV infection by detection of specific antibodies (immunoglobulin M and immunoglobulin G) and/or positive RNA in blood and stool. In four patients serial HEV viral loads in blood were measured. Results: Only one patient reached HEV clearance after reduction of immunosuppressive therapy (predominantly reduction of MPA daily dose) alone, whereas six patients were treated with ribavirin after reduction of immunosuppressive therapy due to persistent virus replication. Four of six patients reached HEV clearance after 3 months of ribavirin therapy. HEV clearance was observed after 34–42 days. Two patients, both treated with rituximab within the last 12 months before diagnosis of HEV infection, needed prolonged ribavirin therapy due to persistent viral replication. Conclusion: Reduction of daily dose of MPA therapy alone in transplant patients with chronic HEV infection may not be sufficient to control viral replication. HEV clearance under ribavirin therapy shows interindividual variability. Therefore, serial viral monitoring may be useful to personalize treatment duration. Rituximab therapy is a risk factor for complicated‐to‐treat chronic HEV infection. Graphical abstract: In this article, hepatitis E virus (HEV) infections in renal transplant recipients were examined. Serial measurements of HEV‐RNA are helpful to determine the optimal duration of ribavirin treatment. We identified previous rituximab treatment to be a risk factor for a prolonged treatment course.